Postural disorders in young athletes - Solovjova, J.; Upitis I.; Grants, J.; Kalmikovs, J. J. (Education. Physical training. Sport, 2014)
Research background and hypothesis. Athletes across all sports face sports injuries stemming from the overuse of specific muscle groups for that particular sport. It was hypothesised that athletes from each sport would show similar muscular-skeletal changes allowing a postural stereotype for each sport to be allocated. The aim of this study was to determine the peculiarities of postural changes of young athletes in accordance with postural tone and phasic contraction muscles. Research methods. The participants of this study were 92 young Latvian athletes aged 14-17 and having different preparation level, i. e. 20 swimmers, 20 ice-hockey players and 19 basketball players, 17 handball players and 16 cyclists. Tests were completed using methods of visual diagnostics (Vassileva, 1996) and muscular functional testing (Kendall, M. O., Kendall, F. P., 1982). Research results. The lower cross syndrome is a common feature for athletes of sports requiring complicated coordination at high rates of workloads on lower extremities. Individual decline from a neutral posture in the sagittal plane is a characteristic feature for individuals of various kinds of sport due to overload of some muscle groups. Discussion and conclusions. The presence of a postural stereotype indicates that these muscular-skeletal changes are beneficial to athletes. How much benefit the athletes gain from these postural changes before injury occurs, is open to debate. It is purposeful to distinguish muscles according to their tone to postural and contracting muscles. The postural muscles that form posture have rather high tone, but if these muscles are overloaded, the tone pathologically increases and the muscle cannot contract nor relax effectively enough to allow the antagonist to work.